1977
DOI: 10.1083/jcb.73.1.161
|View full text |Cite
|
Sign up to set email alerts
|

Membrane fusion during secretion. A hypothesis based on electron microscope observation of Phytophthora Palmivora zoospores during encystment.

Abstract: Interpretation of freeze-fracture and thin-section results shows that fusion of the peripheral vesicle with the plasmalemma of a Phytophthora palmivora zoospore occurs at several discrete sites and results in the formation and expansion of a particle-free bilayer membrane diaphragm and in the appearance of a polymorphic network of membrane-bounded tunnels, the lumina of which are continuous with the cytoplasm. The outer half of the bilayer membrane diaphragm appears continuous with the outer half of the plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

1977
1977
1997
1997

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(39 citation statements)
references
References 30 publications
(32 reference statements)
3
36
0
Order By: Relevance
“…The fracture plane is deflected at the site of each particle and it is this deflection that morphologically determines the particle itself: i.e., the membrane particles are defined relative to, and in contradistinction to, the bilayer continuum of biomembranes. Although in every successfully investigated case integral membrane proteins (and, in consequence, their tightly associated lipids) were shown to be components of the membrane particles, the presence of integral proteins is not, in principle, a necessary condition; micellar subphases sequestered within the polar matrix of the bilayer can also appear, in freeze-fractured preparations, as "particles"-i.e., as local deviations of the fracture plane, albeit with a characteristic morphology (25,26). In many membranes, however, and particularly in specialized membranes (e.g., chloroplast grana) or membrane regions (e.g., gap junctions) interruptions of the bilayer continuum may account for most of the membrane area.…”
Section: Results Ultrastructurementioning
confidence: 99%
“…The fracture plane is deflected at the site of each particle and it is this deflection that morphologically determines the particle itself: i.e., the membrane particles are defined relative to, and in contradistinction to, the bilayer continuum of biomembranes. Although in every successfully investigated case integral membrane proteins (and, in consequence, their tightly associated lipids) were shown to be components of the membrane particles, the presence of integral proteins is not, in principle, a necessary condition; micellar subphases sequestered within the polar matrix of the bilayer can also appear, in freeze-fractured preparations, as "particles"-i.e., as local deviations of the fracture plane, albeit with a characteristic morphology (25,26). In many membranes, however, and particularly in specialized membranes (e.g., chloroplast grana) or membrane regions (e.g., gap junctions) interruptions of the bilayer continuum may account for most of the membrane area.…”
Section: Results Ultrastructurementioning
confidence: 99%
“…Circular clearings of intramembranous particles have been described in various other fusional systems, such as frog neuromuscular junctions, pancreatic islet cells, and Phytophthora zoospores (10,42,46) . It has been argued that these maculae are artifactually produced by either glutaraldehyde or glycerol, for they were not seen in freeze-fracture images of quick-frozen mast cells (12) .…”
Section: Imp Clearingsmentioning
confidence: 99%
“…Initial freeze-fracture experiments [95][96][97] suggested that fusion could proceed only after clearance of the protein particles. It was assumed that regions free of intramembrane particles or at least relatively large exposed bilayer regions were necessary for actual fusion to occur.…”
Section: Vc Membrane Fusionmentioning
confidence: 99%